Impact of type 2 diabetes mellitus on short‐term and long‐term outcomes of patients with esophageal squamous cell cancer undergoing resection: a propensity score analysis. Issue 1 (27th April 2018) - Yao, Wang; Meng, Yuqi; Lu, Mingjian; Fan, Wenzhe; Huang, Jinhua; Li, Jiaping; Zhu, Zhihua
Abstract: Background: The association between type 2 diabetes mellitus (T2DM) and the risk of esophageal cancer remains unclear. The present study aimed to evaluate the impact of T2DM on short‐term outcomes and long‐term survival in patients with esophageal squamous cell cancer (ESCC). Methods: The present retrospective study included 862 patients diagnosed with ESCC between January 2001 and December 2010. Among them, 280 patients had T2DM. A 1:1 propensity score‐matched cohort consisting of 280 patients with and 280 without T2DM was selected from the 862 patients. The associations between T2DM and clinicopathologic characteristics were assessed using the χ 2 or Fisher's exact test. Survival of ESCC patients with and without T2DM was calculated by using the Kaplan–Meier method and compared by using the Cox regression model between the two groups. Results: The occurrence rate of anastomotic leakage was significantly higher in patients with T2DM than in those without T2DM ( P < 0.001). In the subgroup with weight loss rate ≤ 5.05%, ESCC patients with T2DM had a significant longer overall survival than did those without T2DM ( P = 0.003), whereas in the subgroup with weight loss rate > 5.05%, the patients without T2DM showed a longer survival ( P = 0.001). Univariate and multivariate analysis results showed that T2DM was not an independent prognostic factor for patient survival. Conclusions: Type 2 diabetes mellitus is not an independent prognostic factor in patients with ESCC. However, the combination of T2DM with severe weight loss would be a predictor of poor prognosis.